PENGARUH PEMIKIRAN WITTGENSTEIN TERHADAP MATEMATIKA - Suyitno, Hardi (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2007)
Wittgenstein is a unique philosopher. He criticizes his own opinion. Philosophers divide his views in two periods that are early and later. The early of Wittgenteinâ€™s view set by Tractatus Logico Philosophicus and the later set by Philosophical Investigations. Wittgenstein's conceptions of mathematics fall in three periods, that are early, midle and later. The early period Wittgenstein's conception of mathematics set by Tractatus Logico Philosophicus, the midle period set by Philosophical Grammar dan Philosophical Remarks, and the later period set by Remarks on the Foundations of Mathematics. The Wittgensteinâ€™s view on mathematics is not belonging to logicism, formalism, or intuitionism. The later Wittgenstein on mathematics is that â€œMathematics as a human inventionâ€. He maintains his rejection for infinitely in mathematics.